STRATEGI GASTRODIPLOMASI INDONESIA MELALUI PROGRAM CO- BRANDING DIASPORA DI AUSTRALIA TAHUN 2018-2020 - Putri Indah Diahtantri (2021)
As a driver of public diplomacy, the idea of using gastrodiplomacy as a soft power has become a choice taken by several countries, especially Indonesia. This study discusses the Co-Branding Diaspora Restaurant program as one of the efforts in implementing Indonesian gastrodiplomacy that focuses on Australia. This study uses a qualitative method with descriptive analytical research type which is expected to see the role of state and non-state actors in the development of Indonesian gastrodiplomacy and the results obtained from the application of gastrodiplomacy whether it can improve Indonesia's foreign policy. Then the recommendations offered in this research, it is necessary to formulate a comprehensive national strategy to maximize the success of Indonesian gastrodiplomacy in the world, especially in Australia.